Reverse and Inverse Logistic Models for Solid Waste Management - Sepulveda-Salas, J; Carrasco-Armijo, R; Banguera-Arroyo, L; Vargas-Guzman, M; Fuertes-Sanchez, G (South African Institute of Industrial Engineering, 2017)
This paper presents a literature review of different models of reverse and inverse logistics for solid waste management by using the content analysis method. The article has two parts. In the first part, the studies of diverse authors are discussed to define the activities or steps to be followed for a general model of reverse and inverse logistics. These authors establish four basic steps for managing solid waste (gatekeeping, collection, sorting, and disposal). The second part deals with exploratory studies, designs, methodologies, and proposed mathematical models to solve problems in inverse logistics, based on articles published between 2010 and 2016. © 2017, South African Institute of Industrial Engineering. All rights reserved.